Design, analysis and fabrication of dustbin 5R / Faiqah Nadhirah Zaizul Jifri and Norjasween Abdul Malik - Zaizul Jifri, Faiqah Nadhirah; Abdul Malik, Norjasween (School of Mechanical Engineering, 2023)
Malaysia, with its fast-growing population over the years, requires a new alternative to reduce the spread of carbon dioxide and methane gas, both of which are produced by food waste. This project aims to implement the 5R factors into people's daily lives, which are reuse, reduce, recycle, refuse, and rot. The Dustbin 5R project targets users with small gardens in their houses and aims to improve the management of food waste at home. The main objective of this project is to design and fabricate a dustbin that can process food waste generated at home and convert it into organic fertilizer. The dustbin's total dimensions are 500mm x 500mm x 600mm. In conclusion, the product has been successfully fabricated and is functioning well. This 5R dustbin can cut and store up to a maximum capacity of 5kg of food waste. Its main advantage is that it is user-friendly and environmentally friendly. Lastly, this project is expected to help users produce their own organic fertilizer by utilizing the food waste generated at home.